3y2 - 2y + 6xy - 4x = y(3y - 2) + 2x(3y - 2) = (y + 2x)*(3y - 2)
All six of them
I understand this to be y3. Then the derivative is 3y2. If y is considered a so-called 'implicit function' of x then the derivative might be written 3y2 dy/dx.
(3y - 2)(y - 4)
Yes. It is like having a-b, which is a+(-b), which is -b+a, so 3-2y = 3+(-2y) = -2y+3
3y2 - 2y + 6xy - 4x = y(3y - 2) + 2x(3y - 2) = (y + 2x)*(3y - 2)
(5y - 6z)(2y + z)
The given quadratic expression can be factored as (3y+5)(y-1)
All six of them
18x3y5 + 9xy3 - 3xy = 3xy(6x2y4 + 3y2 - 1)
(3y2)4*3y2*3y2*3y2*3y2 = 38*y16 = 6561y16
The GCF is 3y2
xn- yn=(x - y)(xn-1 + xn-2y +xn-3y2 +. . .+x2yn-3+xyn-2 + yn-1)
3y4 + 3y2 = 3y2(y2 + 1)
It is: 12y^7
The GCF is 3.
I understand this to be y3. Then the derivative is 3y2. If y is considered a so-called 'implicit function' of x then the derivative might be written 3y2 dy/dx.